1995
DOI: 10.3109/10428199509059641
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Ferritin in Hematopoiesis and the Immune System

Abstract: Elevated serum ferritin levels have been reported in a number of pathological states. These observations indicate that cells of the immune system can participate in the prevention of potential tissue toxicity from iron accumulation, and iron and iron-binding protein have important effects on immune systems. Ferritin is generally regarded as an intracellular iron storage protein. However, small amounts of ferritin circulate in the serum of normal individuals, and the physiological role of serum ferritin remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 27 publications
1
39
0
Order By: Relevance
“…In contrast, L-ferritin had a small stimulatory effect on anti-CD3-stimulated lymphocytes. Heart ferritin, which is higher in H-ferritin, 21 increased the levels of suppression in a dosedependent manner, whereas liver ferritin, reported to be rich in L-ferritin, 21 did not suppress lymphocyte proliferation. As shown in Figure 8, pre-incubation of increasing concentrations of rLferritin with a constant concentration of H-ferritin (45 M) resulted in inhibition of the suppressive effects induced by H-ferritin.…”
Section: Effects Of H-and L-ferritin On Anti-cd3 Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, L-ferritin had a small stimulatory effect on anti-CD3-stimulated lymphocytes. Heart ferritin, which is higher in H-ferritin, 21 increased the levels of suppression in a dosedependent manner, whereas liver ferritin, reported to be rich in L-ferritin, 21 did not suppress lymphocyte proliferation. As shown in Figure 8, pre-incubation of increasing concentrations of rLferritin with a constant concentration of H-ferritin (45 M) resulted in inhibition of the suppressive effects induced by H-ferritin.…”
Section: Effects Of H-and L-ferritin On Anti-cd3 Responsesmentioning
confidence: 99%
“…Morikawa et al 21 suggested that the biological properties of ferritin might vary depending on the ratio of heavy and light chains. In view of this, H-and L-ferritin expression was examined in melanoma cells and other non-malignant cells by flow cytometry.…”
Section: Eamination Of H-and L-ferritin Expression By Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that the ferritin level at the time of emergence increased in hemolymph compared with pupal hemolymph. In vertebrates, elevated serum ferritin levels have been reported in a number of pathological states (Morikawa et al 1995), and ferritin acts as an immunosuppressor, signaling molecule and immune regulator (Recalcati et al 2008). In Drosophila , overexpression of both the HCH and LCH genes is required to confer protection against oxidative stress (Missirlis et al 2007).…”
Section: Ferritin-a High Abundance Protein In Newly Emerged Honeybeesmentioning
confidence: 99%
“…Ferritin does not have an obvious leader sequence, and the mechanism of its release from cells is unclear. Serum ferritin is increased during inflammation, which suggests that it may play a role in modulating inflammatory effects (2,3). In a recent issue of PNAS, Coffman et al (4) provide compelling evidence that serum ferritin regulates vascular remodeling and angiogenesis, demonstrating a role for serum ferritin in cell proliferation.…”
mentioning
confidence: 98%